Our divided political heart : the battle for the American idea in an age of discontent - Dionne, E. J. (New York : Bloomsbury, 2012)
"One of America's most respected and well-known political analysts weighs in on what is tearing us apart--the ascendancy of individualism and the diminishment of community--just in time for the election. Our Divided Political Heart will be the must-read book of the 2012 election campaign. Offering an incisive analysis of how hyper-individualism is poisoning the nation's political atmosphere, E. J. Dionne Jr. argues that Americans can't agree on who we are because we can't agree on who we've been, or what it is, philosophically and spiritually, that makes us Americans. Dionne takes on the Tea Party's distortions of American history and shows that the true American tradition points not to radical individualism, but to a balance between our love of individualism and our devotion to community. Dionne offers both a fascinating tour of American history--from the Founding Fathers to Clay and Lincoln and on to the Populists, the Progressives and the New Dealers--and also an analysis of our current politics that shatters conventional wisdom. The true American idea, far from endorsing government inaction or indifference, has always viewed the federal government as an active and constructive partner with the rest of society in promoting prosperity, opportunity, and American greatness. The ability of the American system to self-correct is its greatest asset and Dionne challenges progressives to embrace the American story. Our fractious but productive past offers us the resources both to rediscover the idea of progress and to put an end to our fears of decline. Our Divided Political Heart will be required reading for all who seek a path out of our current impasse."--Publisher's website.
Introduction: who we are : liberty, community, and the American character -- Why are we yelling at each other? -- Two cups of tea : the tea party in history and on history -- The politics of history : why the past can never escape the present -- Lessons from the humble penny : the striver, the seeker, the Puritan, and the patriot -- Reinventing American liberalism : why the left embraced community -- From tradition to revolt : how conservatives left community behind -- What history teaches us. -- One nation, conceived in argument : the revolution, the constitution, and the origins of the American debate -- The American system : how strong government, strong individuals, and strong communities have supported each other -- What's the matter with populism? : why everybody loves it, except when they don't -- The long consensus and its achievements : the quest for balance from the Progressive Era to the Reagan Era -- Recovering our balance, restoring our greatness. -- The new American system : building a community of freedom -- A personal note.
Includes bibliographical references (pages 279-313) and index.
Keywords: Political culture -- United States -- History; National characteristics, American; Social values -- United States -- History; United States -- Politics and government -- History; United States -- Politics and government -- 2009-2017.